Using meaningful experiences as a vision for physical education teaching and teacher education practice. (2nd November 2019) - Ní Chróinín, Déirdre; Beni, Stephanie; Fletcher, Tim; Griffin, Ciara; Price, Caitlin
ABSTRACT: Background : Teachers' visions are vivid and concrete images of ideal classroom practices. A vision for teaching is important to both practices in the classroom as well as teacher development across time. A useful tool to explore and analyse the role of vision in teacher practices is provided by [Hammerness, K. 2003. "Learning to Hope, or Hoping to Learn? The Role of Vision in the Early Professional Lives of Teachers." Journal of Teacher Education 54 (1): 43–56], whose framework of vision consists of three dimensions: focus, range and distance. Purpose : The writing of [Kretchmar, R. S. 2000. "Moving and Being Moved: Implications for Practice." Quest 52 (3): 260–272; 2008. "The Increasing Utility of Elementary School Physical Education: A Mixed Blessing and Unique Challenge." The Elementary School Journal 108 (3): 161–170] provides the basis for a vision focused on meaningful experiences in physical education. The purpose of this paper is to describe the ways a vision based on meaningful experiences enabled two teachers and three teacher educators to name, describe, and enact their physical education teaching and teacher education practices. Methodology : Raw data from six separate self-studies of practice involving the five participants provided the starting point for this research. Data sources, including written reflections and critical friend responses as well as audio recordings of conversations with critical friends, were mined to identify examples where vision was represented. Further data were generated in a focus group where participants shared and analysed their experiences and discussed how meaningful physical education served as both an individual and collective vision for practice. A final written reflection allowed participants to articulate their current vision for meaningful physical education. A thematic analysis of all data sources supported the organisation of data into three distinct phases of development of practices with emphasis on the role of vision in each phase. Findings : Over time, there was an evolution in our understanding of both what meaningful physical education consisted of and how we might facilitate meaningful experiences for children. In particular, our visions became clearer and better aligned with our practices. We illustrate how we developed our practice in ways that allowed us to take ownership of this vision, and, in the process, changed who we were as teachers and teacher educators. Finally, we share how the process of exploring and analysing our individual visions allowed us to articulate a shared vision of meaningful physical education and explain how to go about implementing our collective vision in practice. Conclusion : We highlight the value of paying attention to the role of vision in promoting and supporting educators, individually and collectively, in developing and sustaining innovation in teaching and teacher education practice.